Determinar el nivel de presión arterial en estudiantes del bachillerato de la Unidad Educativa Atahualpa del año 2014. - Loayza Sivisapa, Liliana E (2014)
Obesity has become epidemic centuries the incidence and prevalence of hypertension in the early stages of life has increased significantly in both developed countries increasingly become relevant diseases mayor in the early stages of life.